Pengaruh Kompensasi, Motivasi Dan KomitmenTerhadap Kinerja Pegawai Kud Pakis Kabupaten Malang (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThe study aims to determine the effect of leadership, motivation, work environment on the performance of employees of the Village Office of Dau Subdistrict, Malang Regency. Data collection is done by the method of documentation, questionnaires and interviews. The population in this study were all village office employees in Kec. Dau Kab. Malang, a total of 110 with samples using total sample techniques using the Slovin formula, so that the total obtained is 52 people. This study uses quantitative analysis. While the test equipment used is the instrument test, normality, classic assumption, multiple regression analysis using the SPSS version 16.0 program. the results of this study indicate that the instrument used is valid and reliable, also the data obtained is normally distributed using the One sample Kolmogrov Smirnov table value of 0.141. As well as free data from Multicollinearity and Heteroscedasticity. The multiple linear regression results show that the independent variables have a positive effect on the dependent variable, also supported by a significant partial test (t test) which is generated by 0.000 (X1), 0.041 (X2), 0.005 (X3) with a standard of significance 0, 05. thus indicating that good leadership, motivation in employees, a good work environment will affect the performance of employees at the Village office in Dau District, Malang Regency. Kata kunci : Kompensasi, Motivasi, Komitmen terhadap Kinerja Karyawan